2021
DOI: 10.3389/fphar.2021.691995
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Immunomodulatory Activity of a Novel Polysaccharide From Lycopi Herba

Abstract: Lycopi Herba has been broadly used as a traditional medicinal herb in Asia due to its ability to strengthen immunity. However, it is still obscure for its material basis and underlying mechanisms. Polysaccharide, as one of the most important components of most natural herbs, usually contributes to the immunomodulatory ability of herbs. Here, we aimed to detect polysaccharides from Lycopi Herba and examine their potential immunomodulatory activity. A novel polysaccharide (LHPW) was extracted from Lycopi Herba a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…→4)- β -Gal p -(1→ (D), →3,6)- β -Gal p -(1→ (E), and →3)- β -Gal p -(1→ (F) were matched to the signals of δ H /δ C 4.56/105.74, 4.52/104.69 and 4.4/104.48, respectively. Similar signals of anomeric proton and carbon have been reported in some literature [ 26 , 27 ]. Residue G was found to have a downfield H-1 (4.45 ppm) and a downfield C-1 (103.63 ppm), consistent with →4)- β -Glc p -(1→ [ 28 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…→4)- β -Gal p -(1→ (D), →3,6)- β -Gal p -(1→ (E), and →3)- β -Gal p -(1→ (F) were matched to the signals of δ H /δ C 4.56/105.74, 4.52/104.69 and 4.4/104.48, respectively. Similar signals of anomeric proton and carbon have been reported in some literature [ 26 , 27 ]. Residue G was found to have a downfield H-1 (4.45 ppm) and a downfield C-1 (103.63 ppm), consistent with →4)- β -Glc p -(1→ [ 28 ].…”
Section: Resultssupporting
confidence: 88%
“…Of the multitude of immune cells, macrophages are the first line of defense with various activities, such as phagocytosis, surveillance, chemotaxis, and the destruction of targeted organisms [ 26 , 49 ]. Research has shown that a macrophage activation is a promising approach to improving host immune capability and strengthening disease resistance [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Residues C and G were identified as →2,4)- α -L-Rha p -(1→ and α -L-Ara p -(1→ by the anomeric signals at δ H /δ C 5.17/99.5 and 4.98/109.23, respectively [ 32 ]. The residue α -L-Ara f -(1→ (D) was matched with the signal of δ H /δ C 5.08/108.45 [ 7 ]. Residue E was found to have a downfield H-1 (5.04 ppm) and a downfield C-1 (98.7 ppm), consistent with →3,4)- α -D-Glc p -(1→ [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that most polysaccharides-induced actions are dependent on macrophage functional ability [ 6 ]. Macrophages are the first line of defense, with various activities performed by the multitudinous immune cells, such as phagocytosis, surveillance, chemotaxis, and destruction of targeted organisms [ 7 , 8 , 9 ]. Research has been proven that macrophage activation is a promising approach to improve host immune capability and strengthen disease resistance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cell supernatants were collected. TNF-α proteins in the cell supernatants were measured using the ELISA kits (R&D) according to the instructions (19). To determine the effect of RATAPW on the growth profile of RAW264.7 cells, 0.5 mg/ml MTT was added to the plates and further incubated for 4 h at 37 • C. The optical density was measured at 570 nm.…”
Section: Measurement Of Tnf-α Cytokine Production Induced By Ratapwmentioning
confidence: 99%